2015
DOI: 10.1063/1.4907271
|View full text |Cite|
|
Sign up to set email alerts
|

Sub-terahertz spectroscopy reveals that proteins influence the properties of water at greater distances than previously detected

Abstract: Erratum: "Sub-terahertz spectroscopy reveals that proteins influence the properties of water at greater distances than previously detected" [J. Chem. Phys. 142, 055101 (2015) The initial purpose of the study is to systematically investigate the solvation properties of different proteins in water solution by terahertz (THz) radiation absorption. Transmission measurements of protein water solutions have been performed using a vector network analyser-driven quasi-optical bench covering the WR-3 waveguide band (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 60 publications
(87 reference statements)
7
39
0
Order By: Relevance
“…Under these assumptions the resultant average dipole moment induced over the solution, and hence the THz absorption, is further reduced. Previous measurements of proteins (including lysozyme) in water solutions have, however, shown that rather than the THz absorption being lower than expected when considering only water removal, the THz absorption is actually higher [24][25][26][27][28][29], consistent with the results reported here (Fig. 2).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Under these assumptions the resultant average dipole moment induced over the solution, and hence the THz absorption, is further reduced. Previous measurements of proteins (including lysozyme) in water solutions have, however, shown that rather than the THz absorption being lower than expected when considering only water removal, the THz absorption is actually higher [24][25][26][27][28][29], consistent with the results reported here (Fig. 2).…”
supporting
confidence: 92%
“…However, when lower concentrations are used, terahertz techniques suggest that the population of hydration water is much larger and extends over multiple layers. Extended hydration shells, where the effect of the protein on the water molecules is evident, have been reported to vary between 15 Å and 25 Å from the solute surface for different proteins [25][26][27][28][29]. While these works are based on the simplistic assumption that the absorption coefficient of a complex system can always be written as the weighted sum of the absorption of its components [35], here we show how determining the complex dielectric response provides a much more informative and reliable assessment of the impact of protein-water interactions on the water environment.…”
mentioning
confidence: 99%
“…In this context, it is important to keep in mind that the magnitude of the extent of the hydration shell is sensitive to the frequency that is used to calculate its value. In this work we have fixed the frequency to 1 THz, whereas other groups have used frequencies between 0.2 and 2.5 THz for similar analysis . In this frequency range, the terahertz spectra exhibit losses because of the structural dielectric relaxations (these contributions decrease with frequency) as well as librational/vibrational motions (increasing losses with frequency) .…”
Section: Discussionmentioning
confidence: 99%
“…Due to its distinctive spectral responses to THz radiation, the dynamic hydration shell can be precisely determined by probing protein-induced fast solvation dynamics by THz spectroscopy [4]. A broader hydration shell than previously determined by molecular dynamics simulations has been detected by THz spectroscopy, highlighting its potential for estimating protein hydrophobicity [28]. In addition, the protein-ligand binding between hen egg white lysozyme (HEWL) and triacetylglucosamine (3NAG) was successfully probed at 270 K [29], showing that HEWL + 3NAG has smaller absorption coefficients than free HEWL ( Figure 2C) and proving the feasibility of monitoring protein-ligand binding in solution using THz spectroscopy.…”
Section: Proteinsmentioning
confidence: 99%